InSAR (from Sentinel 1) Teil (France) EQ Nov, 2019 - Antoine Lucas (PANGAEA, 2025)
The post-seismic displacement that occurred after the Nov. 11 2019 of Teil (France), located at 44°31'04''N, 4°40'15''E, and with a moment magnitude of 4.9 has been derived from InSAR technique after two ESA Sentinel-1 observations. The InSAR is computed from master image of the Nov. 6 and slave image of the Nov. 12 2019. The InSAR processing is done from the VV polarization, and has been performed with SNAP. The data set contains the displacement measurements expressed in meters. The data set is coded in 32 bit floats in a Geotiff file using a geographical grid using WGS-84 ellipsoid (EPSG:4326). The spatial sampling corresponds approximately to 11.7 m/pixel.